Gangguan Mental Pada Remaja Era Gen Z Sebagai Ide Penciptaan Karya Seni Lukis Digital - Prasetyo, Venessa Rahma; Prasetyo, Abdul Rahman (Mahesa Research Center, 2025)
Gen Z teens are prone to mental disorders such as anxiety and depression due to social pressure and digital exposure. The lack of mental health awareness exacerbates their emotional state. This research aims to realize the issue into digital painting artworks. This study tries to define the concept, method, and depict the notion idea of digital painting with the theme of mental disorders in Gen Z teenagers. The method used is the creation of works based on the Alma M. Hawkins model which consists of three stages: exploration, improvisation, and realization. Visualization was done using Clip Studio Paint and Adobe Illustrator software to produce six digital paintings. These works depict various mental disorders such as depression, bipolar, trauma, insomnia, anxiety, and eating disorders, which are applied in the form of stickers on laptop covers. This media was selected since it is related to our everyday life of Gen Z teenagers and effective as a means of self-expression. Practically, this creation can be utilized in art-based education and therapy for teenagers. Theoretically, this work enriches the study of digital art that is contextual to the psychological issues of Gen Z.